GeoGebra Sebagai Aplikasi Visual untuk Topik Turunan dan Integral di MGMP Matematika SMA Kabupaten Purbalingga - Nunung Nurhayati; Siti Rahmah Nurshiami; Renny Renny; Rina Reorita; Sri Maryani (AMMA : Jurnal Pengabdian Masyarakat, 2023)
GeoGebra is an interactive geometry software that supports the implementation of mathematics learning. With this software, it is hoped that students' interest in getting to know mathematics more closely will increase through mathematical experiments. GeoGebra can be used not only by students but can also be used by teachers as educators. At present teachers are required to be able to keep up with technological advances, this is in line with RI Law no. 14 of 2005 in terms of increasing the professional competence of teachers. The Covid-19 pandemic has brought changes in terms of interacting with technology. This has a positive impact on teachers as educators. GeoGebra for math teachers is a technological innovation that strongly supports mathematics learning. The GeoGebra application can provide mathematical visualization so that teachers as educators and students as students will find it easier to understand deeper mathematical material. Several math topics exist in senior secondary schools and require visualization to make them easier to understand, including derivative and integral material. Mathematics which is introduced at the high school level (SMA) requires reasoning, visualization and imagination in understanding the concepts of limits and derivatives. This community service (PKM) provides GeoGebra training to high school Mathematics MGMP teachers in Purbalingga Regency for derivative and integral topics. First, high school mathematics MGMP teachers in Purbalingga district were given a pre-test and post-test regarding initial knowledge of derivatives and integrals from 24 representatives of mathematics teachers in Purbalingga district. The results of the pre-test showed that 60.83% of mathematics teachers could answer each point correctly, while the results of the post-test showed an increase in teachers' understanding of derivative and integral topics, namely 80.78% of mathematics teachers were able to answer each point correctly. questions asked. Based on these data, it can be seen that the GeoGebra training provided during this PKM increased the ability of mathematics teachers to understand GeoGebra for derivative and integral topics by 19.95%.